LABOR FORCE PARTICIPATION TRENDS: DOES SOCIO-DEMOGRAPHIC MATTERS? STUDY CASE IN BREBES DURING 2011-2023 - Maulana Ghani Yusuf; Navi'ah Khusniati (Transpublika Publisher, 2025)
Brebes Regency is the regency with the largest population in Central Java. This regency faces major challenges in the employment sector, namely the condition of the Labor Force Participation Rate (LFPP) which is in the third lowest position among regencies/cities in Central Java. The low LFPP figure shows that many working-age residents are not absorbed in economic activities. The situation is worsened by the alarming rate of joblessness, which ranks second only to Tegal City, and the poor Human Development Index (HDI) ranking in Central Java. The main objective of this research is to examine the patterns and factors that impact the involvement of the workforce in Brebes Regency from 2011 to 2023. Employing a quantitative method, this research seeks to identify how sociodemographic elements influence labor force participation in Brebes Regency. Multiple linear regression analysis was utilized in this study to examine the connection between variables by employing SPSS software. The regression results indicated a significance level of 0.001 and an F value of 14.202. These findings suggest that sociodemographic factors collectively play a significant role in influencing labor force participation in Brebes Regency. Partially, the sociodemographic factor that has the highest significant influence is the HDI. Based on these findings, improving the quality of education and health is the government's main focus so that workforce participation can be more optimal. Thus, it is hoped that the high population can be utilized to increase regional development in Brebes Regency which is reflected in the high level of workforce participation.